Malory's Le Morte D'Arthur King Arthur and the legends of the round table : the classic rendition - Malory, Thomas Sir 15th cent (Signet Classic, 2001)
Presents the epic story of King Arthur, the wizard Merlin, his Knights of the Round Table, the sword Excalibur, and his tragic and poetic death, in a prose translation of the classic legend, featuring an introduction by acclaimed poet Robert Graves.